Pola Komunikasi Anggota Keluarga Dengan Penyandang Stroke Iskemik Sebagai Upaya Pemulihan - Baihaqi, M Novan; Suminar, Jenny Ratna; Prasanti, Ditha (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
The nuclear family is the closest person who helps meet the daily needs of ischemic stroke sufferers. In their lives, ischemic stroke sufferers cannot be separated from interaction and communication with family members. The purpose of this study are: 1). To find out the interactions of family members with ischemic stroke as a recovery effort, 2). Knowing the reasons for communication with family members for ischemic stroke patient is needed as a recovery. This research is a qualitative with a case study approach. The data collection technique used observation and in-depth interviews. The number of resource persons is eight people consisting of six family members as resource persons and two health experts as well a stroke physiotherapist and a neurologist. This research uses Symbolic Interaction theory as a result analysis tool. The results showed that: 1). Interaction carried out by family members with people with ischemic stroke as recovery effort begins with involvement of all family members interacting with people with ischemic stroke regarding, daily activities, feelings and emotions of people with ischemic stroke, entertainment, and motivational sentences, then there are communication barriers, 2) The reasons for communicating with family members for people with ischemic stroke are needed as recovery effort, namely the patient feels more cared for, gives encouragement and motivation to recover in the patient, raises the patient's passion for life/mood, pays attention to healthy lifestyle, reduces the burden on the mind.